The Role of Distance Learning to Relationships and Family Conflicts in Light of the Corona Virus Among a Sample of University Students in Northern Jordan - Momani, Mohammad Ali; Al-Khatib, Faryal Youssef; Aldiwyry, Fikri Eayid (Journal of Educational and Psychological Sciences, 2022)
: The study aimed at exploring the differences of the family relations and conflicts at a sample of universities students in northern Jordan in light of some variables. The sample consisted of (1243) students. The scale of family relations and conflicts was used in this study, and the current study followed the descriptive approach in one of the analytical forms The results of the study showed statically significant differences in the level of the family relations and conflicts according to the gender variable in favor of males. Besides, differences in the family psychological problems according to the specialties in favor of scientific specialties. And differences in the family behavioral problems according to the variable of human specialties, while there were no statically significant differences in the level of family psychological problems according to the residence variable. The results also showed statically significant differences in the level of family behavioral problems in favor of city students. In addition to a statically significant difference in the level of the family relations and conflicts in favor of first year students as well the variable of distance learning in favor of the duration (more than 7hrs). However there were no statically significant difference s in the level of family relations and conflicts according to the variable of University.
Keywords: Distance Learning; Family Relationships and Conflicts; Corona Virus; University Students; Northern Jordan